Non-Bumiputera Business Organisation in Construction Industry: Success Factors and its Challenges - Janipha, Nurul Afida Isnaini; Mohd Zamri, Nur Fitri Adlin; Judi, Siti Suhana (International Journal of Sustainable Construction Engineering and Technology, 2021)
Achieving success is a highly critical issue for companies to survive, especially for Non-Bumiputera. The large projects in Malaysia construction industry continues to be developed by Non-Bumiputera organisations. In a competitive business environment, success was the ultimate goal of every business organisation. However, there were lacks of research highlighted on the level of success for Non-Bumiputera business organisation in Malaysia construction industry. Therefore, this paper aims to determine the achievement aspects for Non- Bumiputera business organisation in Malaysia construction industry. The objectives supported the aims were; to identify success factors of Non-Bumiputera organisations in Malaysia and to investigate the challenges in their business organisations. An extensive literature review was done to obtain the success factors of business organisations. Questionnaire surveys were distributed to know in depth the success factors and challenges occur in the Non-Bumiputera business organisations. A total of 20 surveys were distributed and 15 responses obtained from the top 20 property developers in 2020 taken from several business property websites and findings were analysed by using SPSS software. Findings revealed that the success factor in the organisation consists of four main criteria; management and organisation, communications, planning and financing. The issue that can be identified comprises of, but, not limited to registration process with the CIDB, financial constraints, risks and communication barriers. Since the construction industry is constantly changing with the development of new business approaches and technologies, business organisations must therefore develop effective strategies to be more competitive in today’s market and to be successful in business.